Naprężenia Momentowe w Tarczy Kołowej - Usidus, C. (Engineering Transactions, 1973)
This paper represents an attempt at quantitative analysis of the influence of couple stresses on the stress distribution in a circular disk (plane strain). The analysis is based on two particular examples of the disk boundary loading: by forces uniformly distributed over a portion of the boundary, and by concentrated forces. Each of the cases is considered for three different models of the solid: the classical elastic body, the medium with constrained rotations and the micropolar body possessing three additional degrees of freedom. Two stress functions are introduced: the Airy stress function and the auxiliary stress function Y. Numerical analysis is performed on a computer. It is shown that the existence of couple stresses may lead to considerable modifications in the state of stress inside the disk, depending upon the values of the additional material constants of the micropolar medium.